Metrology of metasurfaces: optical properties - Nicolas Kossowski; Yanel Tahmi; Amir Loucif; Martin Lepers; Benoit Wattellier; Guillaume Vienne; Samira Khadir; Patrice Genevet (npj Nanophotonics, 2025)
Abstract Optical Metasurfaces (MSs), a new class of planar optical elements, are profoundly disrupting the field of optical design, notably due to their compactness, multi-functionalities, and device integrability. Relying on planar nanofabrication processes closely akin to the semiconductor industry, metasurface technology could benefit from cost-effective and potentially large-scale fabrication techniques forthwith. However, manufacturing metasurfaces with higher levels of complexity in foundries, and assembling them in production lines, still requires comprehensive optical metrology solutions, associated with established standardized measurements, that can validate their functionalities during and after integration into a system. Here, we first review the existing optical metrology techniques previously used for metasurface inspection, including intensity, polarization, quantitative phase measurements, and ptychographic imaging. We finally discuss new perspectives and exciting trends in metasurface designs, trying to identify the disruptive roles they could play in endowing next-generation metrology systems with improved performance and enhanced measurement functionalities.